Registration of 'TAM 305' Hard Red Winter Wheat. Issue 3 (8th May 2015) - Ibrahim, Amir M.H.; Rudd, Jackie; Devkota, Ravindra; Baker, Jason; Sutton, Russell; Simoneaux, Bryan; Opeña, Geraldine; Herrington, Rex; Rooney, Lloyd; Dykes, Linda; Awika, Joseph; Nelson, Lloyd R.; et al.
Abstract : Leaf and stripe rusts (caused by Puccinia triticina Erikss. and P. striiformis Westend. f. sp. tritici Erikss., respectively) are major disease problems in South Texas, Rolling Plains, and the Blacklands area of Texas where hard red winter wheat (HRW; Triticum aestivum L.) is a major crop, and wheat producers in these areas require rust‐resistant cultivars. A significant breeding objective in South Texas is to develop HRW cultivars with robust resistance to both rust pathogens. Among these HRW cultivars is 'TAM 305' (Reg. No. CV‐1108, PI 674514), which was developed and released by Texas A&M AgriLife Research in 2012. TAM 305 was derived from the cross TX97V3006/TX98V6239. The original cross, designated X00VC230, was made at College Station, TX, in 1999. TAM 305 was released not only for its leaf, stripe, and stem rust (caused by P. graminis Pers.:Pers. f. sp. tritici Erikss. & E. Henn.) resistance but also because of its excellent grain yield in the Blacklands and South Texas. Milling and baking quality characteristics of TAM 305 were rated by the USDA–ARS‐Hard Winter Wheat Quality Laboratory in Manhattan, KS. Comparisons to the HRW quality targets showed that TAM 305 has average milling yield, very good wheat and flour protein, minimal mixing time, excellent water absorption and loaf volume, but below average mixing tolerance.